2012
DOI: 10.1186/1687-1499-2012-260
|View full text |Cite
|
Sign up to set email alerts
|

Distributed joint source-channel coding for relay systems exploiting source-relay correlation and source memory

Abstract: In this article, we propose a distributed joint source-channel coding (DJSCC) technique that well exploits source-relay correlation as well as source memory structure simultaneously for transmitting binary Markov sources in a one-way relay system. The relay only extracts and forwards the source message to the destination, which implies imperfect decoding at the relay. The probability of errors occurring in the source-relay link can be regarded as source-relay correlation. The source-relay correlation can be es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In cooperative communication transmitting users use one another's antenna to realize the benefit of multiple antenna transmission. There are many cooperative strategies to achieve efficient node cooperation, such as amplify and forward [24], decode and forward [5], and coded cooperation [6, 7]. In amplify and forward protocol, relay nodes retransmit amplified versions of the signal received from source.…”
Section: Introductionmentioning
confidence: 99%
“…In cooperative communication transmitting users use one another's antenna to realize the benefit of multiple antenna transmission. There are many cooperative strategies to achieve efficient node cooperation, such as amplify and forward [24], decode and forward [5], and coded cooperation [6, 7]. In amplify and forward protocol, relay nodes retransmit amplified versions of the signal received from source.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [18] use doped accumulator on the top of a bit interleaved coded modulation with iterative detection (BICM-ID) structure such that the EXIT curve matches more closely with outer decoder. In [19] authors use doped accumulator for achieving turbo-cliff. We have used this property of accumulator to obtain iteration gain in cascade of stages comprising of SISO arithmetic decoder.…”
Section: Proposed Scheme 31 System Modelmentioning
confidence: 99%
“…Online estimation of the correlation parameters is one of the promising solutions for practical DJSCC dispensing with the knowledge of correlation at the receiver. Estimation of the spatial-only correlation parameter has been addressed in [7], [8], [11] and high accuracy in estimating the spatial correlation was attained.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the authors of [8]- [10] exploited the spatio-temporal correlation of the sources and demonstrated that further performance improvements can be achieved by exploiting both the spatial and temporal correlations, as compared to spatial correlation only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation